PENGARUH KEPERCAYAAN PADA PEMERINTAH, INSENTIF PAJAK DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Ronaa Saniyyah; Nur aini Rokhmania (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the effect of trust in government, tax incentives and tax knowledge on taxpayer compliance. With a quantitative approach, this research focuses on MSMEs operating in Gubeng District, Surabaya City. The sample was selected using purposive sampling method, with a total of 126 respondents. Data was collected by distributing questionnaires directly through visits to MSME business locations. Data analysis was conducted using Partial Least Square (PLS) with WarpPLS 8.0 software. The results showed that trust in government has no influence on taxpayer compliance. Tax incentives affect taxpayer compliance. Tax knowledge has no effect on taxpayer compliance.